Infrared Thermography in Detecting Peripheral Arterial Disease in Diabetic Foot: A Scoping Review - Adiantara, Ken Rangga Galang; Kristianto, Heri; Yueniwati, Yuyun (Syntax Corporation Indonesia, 2024)
Early and accurate assessment of peripheral arterial disease (PAD) is crucial given its fatal complications such as amputation. Infrared thermography (IRT) offers various advantages in studying PAD. This study aims to map the use of Infrared thermography in detecting Peripheral Arterial Disease in diabetic feet. This review applies the scoping review method to review the literature related to Infrared thermography in detecting vascular disorders in diabetic legs. Article searches are conducted on five databases, namely Google Scholar, PubMed, EBSCO, ScienceDirect, and ProQuest. The Boolean keywords and codes used are